Phosphorus Cycle and Primary Productivity Changes in the Tethys Ocean During the Permian-Triassic Transition: Starving Marine Ecosystems - Müller, Johann; Sun, Yadong; Yang, Fen; Fantasia, Alicia; Joachimski, Michael (Frontiers in Earth Science, 2022)
The ultimate cause(s) of the end-Permian mass extinction (∼252 Ma ago) has been disputed. A complex interplay of various effects, rather than a single, universal killing mechanism, were most likely involved. Climate warming as consequence of greenhouse gas emissions by contemporaneous Siberian Traps volcanism is widely accepted as an initial trigger. Synergetic effects of global warming include increasing stratification of the oceans, inefficient water column mixing, and eventually low marine primary productivity culminating in a series of consequences for higher trophic levels. To explore this scenario in the context of the end-Permian mass extinction, we investigated sedimentary total organic carbon, phosphorus speciation as well as nickel concentrations in two low-latitude Tethyan carbonate sections spanning the Permian-Triassic transition. Total organic carbon, reactive phosphorus and nickel concentrations all decrease in the latest Permian and are low during the Early Triassic, pointing to a decline in primary productivity within the Tethyan realm. We suggest that the productivity collapse started in the upper C. yini conodont Zone, approximately 30 ka prior to the main marine extinction interval. Reduced primary productivity would have resulted in food shortage and thus may serve as explanation for pre-mass extinction perturbations among marine heterotrophic organisms.